An Ion‐Dipole‐Reinforced Polyether Electrolyte with Ion‐Solvation Cages Enabling High–Voltage‐Tolerant and Ion‐Conductive Solid‐State Lithium Metal Batteries. (16th October 2021) - Zhang, Kun; Wu, Feng; Wang, Xinran; Zheng, Lumin; Yang, Xiaoyu; Zhao, Huichun; Sun, Yuheng; Zhao, Wenbin; Bai, Ying; Wu, Chuan
Abstract: Solid‐state electrolytes (SSEs) with sufficient ionic conduction, wide voltage window, flexible‐rigid interface, and ease of processibility are determinative to the development of energy‐dense solid‐state lithium metal batteries. Due to the low density and interfacial compatibility, polyether SSE has been studied for decades but remains handicapped by the inherently low ionic conductivity and insufficient voltage window. In this contribution, an ion‐dipole‐reinforced poly‐3‐hydroxymethyl‐3‐methyloxetane is demonstrated as a novel SSE and major substitution to conventional poly(ethylene oxide). By further polypropylene skeleton compositing, the composite solid electrolyte (PHMP) synergistically achieves high voltage tolerance (4.6 V), high ion‐conduction (25 °C, 1.26 × 10 −4 S cm −1 ), and flexible‐rigid mechanical properties. Cryo‐transmission electron microscope has revealed a columnar Li deposition and LiF‐rich solid electrolyte interface, suggesting excellent dendrite suppression. According to density functional theory, the densely branched ether–oxygen groups play an important role as ion solvation cages, favoring strong Li + ‐coordination and fast diffusion kinetics. More importantly, it restrains the proton‐induced decomposition and essentially enhances high‐voltage stability. As a result, PHMP contributes to an improved rate capability, significantly reduced interface impedance, and long‐term cycle stability of Li symmetrical batteries for over 1600 h. PHMP‐modified LiNi0.8 Co0.1 Mn0.1 O2 |Li batteries exhibit a high discharge capacity of 211.5 mAh g −1 and desirable cycle stability. Abstract : An ion‐dipole‐reinforced composite solid electrolyte (PHMP) is proposed, synergistically achieving high‐voltage stability (4.6 V), high ion‐conduction (25 °C, 1.26 × 10 −4 S cm −1 ), flexible‐rigid mechanical properties, and dendrite suppression. The unique structure facilitates salt dissociation and ion diffusion and restrains proton‐induced high‐voltage decomposition. The structural designability and controllability of hyperbranched polyether solid electrolyte provide fresh insights into solid‐state lithium metal batteries.